Modelling and numerical simulation of the recent outbreak of Ebola - Rachah, Amira
We present a mathematical model that describes one of the most virulent pathogens for humans - the Ebola virus. The spread of this lethal virus is investigated by the SEIR (Susceptible, Exposed, Infectious, Recovered) model. We discuss and simulate the model and then control the evolution of the Ebola virus with the goal to study the impact of vaccination on its spread.